Ironi di Balik Kata “Gila” Pada Cerpen dan Film Pendek Tak Ada yang Gila di Kota Ini - Kusuma, Iswahyudi Candra (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to explain the irony in the short story and film Tak Ada yang Gila di Kota Ini and to see the changes in elements of the short story Tak Ada yang Gila di Kota Ini by Eka Kurniawan and the short film Tak Ada yang Gila di Kota Ini by Wregas Bhanuteja. The method used in this study is the comparative literature method with a sociology of literature approach. The object of study in this study is the short story Tak Ada Yang Gila Di Kota Ini which is found in the short story collection entitled Cinta Tak Ada Mati by Eka Kurniawan published by Gramedia Pustaka Utama in 2005 and the film Tak Ada yang Gila di Kota Ini produced by Rekata Studio. The results of this study are the irony depicted in the short story and short film Tak Ada yang Gila di Kota Ini in the form of the behavior of sane people who are more insane than insane people (ODGJ). In addition, there are changes in elements in the form of reductions, additions, and various changes.